Higher order aberrations and axial elongation in combined 0.01% atropine with orthokeratology for myopia control. (5th September 2020) - Vincent, Stephen J; Tan, Qi; Ng, Alex L K; Cheng, George P M; Woo, Victor C P; Cho, Pauline
Abstract: Purpose: To compare the changes in higher order aberrations (HOA's) for photopic and mesopic pupil diameters in children undergoing orthokeratology treatment (OK) or combined 0.01% atropine with orthokeratology treatment (AOK), and their association with axial elongation. Methods: Children aged 6 to <11 years with 1.00–4.00 D of myopia were randomly assigned to each treatment group. Photopic and mesopic pupil diameters were quantified using automated pupillometry and HOA's were measured with a Hartmann‐Shack aberrometer and Badal system to control for accommodation. HOA's were rescaled to photopic and mesopic pupil diameters and fitted with a 6 th order Zernike polynomial expansion. Axial length was measured using an optical biometer under cycloplegia. Results: Baseline and six‐month data from 25 AOK and 28 OK participants were analysed. At the six‐month visit, pupil diameter was larger in the AOK group under photopic conditions (3.70 ± 0.42 vs 3.12 ± 0.33 mm, p  < 0.001), along with a range of HOA metrics [3 rd to 6 th order and higher order root mean square error values (HO RMS), all p  ≤ 0.003] and individual Zernike terms (primary spherical aberration, and oblique quadrafoil, both p  ≤ 0.03). Axial elongation was greater in the OK treatment group (0.05 ± 0.08 vs −0.01 ± 0.12 mm, p  = 0.02). In the AOK group, axial elongation was correlated with the increase in photopic pupil diameter ( r  = −0.45, p  = 0.02) and with several HOA metrics; however, these associations were not observed in the OK group. Conclusion: AOK treatment resulted in increased photopic pupil size and HOA's, and significantly less axial elongation over a six‐month period compared to OK treatment alone. The improved myopia control observed with combination 0.01% atropine and orthokeratology may be a result of an enhanced optical effect due to a larger photopic pupil size.